Risk of newly diagnosed interstitial lung disease after COVID-19 and impact of vaccination: a nationwide population-based cohort study - Bo-Guen Kim; Hyun Lee; Cho Yun Jeong; Sang Woo Yeom; Dong Won Park; Tai Sun Park; Ji-Yong Moon; Tae-Hyung Kim; Jang Won Sohn; Ho Joo Yoon; Jong Seung Kim; Jong Seung Kim; et al. (Frontiers Media S.A., 2024)
ObjectivesPrevious studies suggested that coronavirus disease 2019 (COVID-19) could lead to pulmonary fibrosis, but the incidence of newly diagnosed interstitial lung disease (ILD) after COVID-19 is unclear. We aimed to determine whether COVID-19 increases the risk of newly diagnosed ILD and whether vaccination against COVID-19 can reduce this risk.MethodsThis retrospective cohort study used data from the Korean National Health Insurance claim-based database. Two study groups and propensity score (PS)-matched control groups were constructed: Study 1: participants diagnosed with COVID-19 (COVID-19 cohort) and their PS-matched controls; Study 2: COVID-19 vaccinated participants (vaccination cohort) and their PS-matched controls.ResultsIn Study 1, during a median 6 months of follow-up, 0.50% of the COVID-19 cohort (300/60,518) and 0.04% of controls (27/60,518) developed newly diagnosed ILD, with an incidence of 9.76 and 0.88 per 1,000 person-years, respectively. The COVID-19 cohort had a higher risk of ILD [adjusted hazard ratio (aHR), 11.01; 95% confidence interval (CI), 7.42-16.32] than controls. In Study 2, the vaccination cohort had a lower risk of newly diagnosed ILD than controls (aHR, 0.44; 95% CI, 0.34-0.57).ConclusionUsing nationwide data, we demonstrated that COVID-19 was associated with a higher incidence rate of newly diagnosed ILD, but that this risk could be mitigated by COVID-19 vaccination.